2001
DOI: 10.1182/blood.v97.7.2098
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence, transcription map, and mutation analysis of the 13q14 chromosomal region deleted in B-cell chronic lymphocytic leukemia

Abstract: IntroductionB-cell chronic lymphocytic leukemia (B-CLL) represents the most common leukemia in the Western countries with an estimated incidence of 1 per 100 000 per year. The disease is characterized by the monoclonal expansion of B lymphocytes expressing the CD5 marker and exhibiting a long life span, possibly because of a perturbed apoptotic program. 1 Current knowledge of the molecular pathogenesis of B-CLL is limited because no specific genetic alteration has yet been associated with this disease. In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
132
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(137 citation statements)
references
References 52 publications
(67 reference statements)
4
132
0
1
Order By: Relevance
“…A number of years ago, several laboratories used positional cloning and sequencing of a region of 41 Mb at the deleted region to identify a tumor-suppressor gene at 13q14. 8,9 Detailed genetic analysis of protein-coding genes located in or close to the deleted region, including loss of heterozygosity (LOH) studies, mutation, and expression analysis, failed to show that any of these genes can function as tumor suppressors. And none of these known genes were found inactivated in CLL by mutations or deletions.…”
Section: Mir-15/16 At 13q14 Gene Discoverymentioning
confidence: 99%
See 2 more Smart Citations
“…A number of years ago, several laboratories used positional cloning and sequencing of a region of 41 Mb at the deleted region to identify a tumor-suppressor gene at 13q14. 8,9 Detailed genetic analysis of protein-coding genes located in or close to the deleted region, including loss of heterozygosity (LOH) studies, mutation, and expression analysis, failed to show that any of these genes can function as tumor suppressors. And none of these known genes were found inactivated in CLL by mutations or deletions.…”
Section: Mir-15/16 At 13q14 Gene Discoverymentioning
confidence: 99%
“…And none of these known genes were found inactivated in CLL by mutations or deletions. [8][9][10][11] In 2001, we generated somatic cell hybrids between mouse and CLLs cells carrying 13q14 deletion and translocation. Analysis of these hybrids revealed that 13q14 tumor-suppressor gene lies within a 30-kb region between exons 2 and 5 of the DLEU2 gene ( Figure 1).…”
Section: Mir-15/16 At 13q14 Gene Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…At present, a few candidate genes have been identified in the 13q14 region; however, it is not known if they are disease-related. 17,18 The presence of 13q14 deletions in both chronic lymphocytic leukemia and mantle cell lymphoma may indicate a common genetic component involved in the tumorigenesis of the two malignancies. Another possible mechanism is that different, but closely linked genes may be involved.…”
Section: Discussionmentioning
confidence: 99%
“…3 Characterization of variable heavy chain (V H ) gene usage has recently been performed in mantle cell lymphoma, revealing that two particular V H gene segments of the immunoglobulin (Ig) locus were preferentially used, namely V H 3-21 (18%) and V H 4-34 (16%). 2,6 Interestingly, the tumor samples with V H 3-21 gene usage almost exclusively expressed lambda light chains, and also in most cases utilized the same V l light chain gene (V l [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. 6 In addition, this group has been shown to have a significantly better prognosis in one report and in other studies displayed a clear tendency towards improved survival compared to mantle cell lymphomas utilizing other V H genes.…”
mentioning
confidence: 99%